Investigation of supramolecular interactions between liquid crystals and PCBM for improved morphological stability in solar cells. (7th October 2016) - Zhou, Weihua; Hu, Kunxing; Shen, Xingxing; Xie, Yuanpeng; Zhang, Lin; Ai, Qingyun; Yin, Jingping; Chen, Yiwang
Abstract : Supramolecular interactions between liquid crystals and PC61 BM restrict the aggregation of PC61 BM for improved morphological stability, depending on the chemical structure. Abstract : Supramolecular interactions between liquid crystals (LCs) of different chemical structures and PC61 BM molecules have been studied, showing that 4-cyano-4′-pentylterphenyl (5CT) containing electron-withdrawing cyano substituents on the phenyl ring exhibited the strongest interactions with PC61 BM, as revealed via density functional theory (DFT) calculations and experimental analysis based on Fourier transform infrared spectrometry (FTIR), differential scanning calorimetry (DSC) and polarized optical microscopy (POM). In contrast, 4-octyloxy-4′-cyanobiphenyl (8OCB) comprising an electro-donating octyloxyl group and dioctylterthiophene (8TTP8) with thiophene rings and long alkyl groups showed weaker interactions with PC61 BM. After electric field treatment at 600 V mm −1 in an air environment, the P3HT:PC61 BM:8OCB specimen showed a higher power conversion efficiency (PCE) of 2.9% and a more stable morphology than P3HT:PC61 BM:8TTP8 with a PCE of 2.7%. Upon annealing at 150 °C for 1 h, 5CT is most effective in restricting the aggregation and crystallization of PC61 BM molecules, thus stabilizing the morphology of P3HT:PC61 BM. Moreover, the supramolecular interaction between LCs and PCBM could also influence the thermal stability in the narrow bandgap system of PTB7-Th:PC71 BM, with 8TTP8 showing the highest ability to restrict the depression of the PCE value.